2015
DOI: 10.1039/c5ta03955j
|View full text |Cite
|
Sign up to set email alerts
|

In situ preparation of N–ZnO/graphene nanocomposites: excellent candidate as a photocatalyst for enhanced solar hydrogen generation and high performance supercapacitor electrode

Abstract: We have demonstrated a facile in situ wet chemical method to synthesize nanostructured nitrogen doped ZnO/Graphene (N-ZnO/GR) nanocomposites for the first time. Nitrogen doped ZnO over graphene (N-ZnO/GR) was studied using various concentrations of graphene. During the synthesis of N-ZnO/GR nanocomposites, in situ formation of graphene via GO reduction and formation of 4-9 nm N-ZnO have been demonstrated. The composite N-ZnO/GR absorbs in the visible region and this property is used for the photocatalytic reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 103 publications
(77 reference statements)
1
57
0
Order By: Relevance
“…3a)36. Obviously, the ZnO nanofiber sample (3.25 eV) is much higher than Mn 2+ -doped samples, but a little lower than the theoretical value (3.37 eV), which may be affected by the nanometer size effect19. And the bandgaps for Mn-ZnO nanofibers are further narrowed by an increased loading (see Table S2).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…3a)36. Obviously, the ZnO nanofiber sample (3.25 eV) is much higher than Mn 2+ -doped samples, but a little lower than the theoretical value (3.37 eV), which may be affected by the nanometer size effect19. And the bandgaps for Mn-ZnO nanofibers are further narrowed by an increased loading (see Table S2).…”
Section: Resultsmentioning
confidence: 89%
“…They could trap the charge carriers shallowly and efficiently to facilitate the detrapping process of charge carriers to the surface of the catalyst which accelerate the interfacial charge transfer processes17. Moreover, previous studies of N-doped TiO 2 or ZnO have shown a significant red shift in light absorption wavelength and notable improvement in photocatalytic activity141819. Here we report a significant enhancement in visible-light photocatalytic activity of ZnO by creating intentional defects in its crystal lattice via Mn 2+ -doping and N 2 atmosphere annealing.…”
mentioning
confidence: 99%
“…It is well known that PL emission intensity results from the recombination of photogenerated charge carriers in semiconductor materials. 53 Figure 12b presents the PL emission spectra measured at room temperature. The excitation wavelength was chosen to be 372 nm, as the UV-vis spectrum of ZnO NR exhibit a strong absorption peak at this wavelength (Figure 12a).…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
“…In the present study, we used ZnO due to its interesting physico‐chemical properties with a band gap of 3.37 eV, which is not effective for visible light‐driven photocatalysis . ZnO is characterized by a high exciton binding energy (60 meV) and piezoelectricity at room temperature .…”
Section: Introductionmentioning
confidence: 99%